The link between the Dirac's method and the Hamilton-Jacobi method for second order Hamiltonian constrained systems (Journal of the College of Basic Education, 2022)
The link between the Dirac's method and the Hamilton-Jacobi method for second order constrained systems is studied. It is shown that the Dirac's method is always in exact agreement with the Hamilton-Jacobi method. The integrability conditions in the Hamilton-Jacobi method are equivalent to the consistency conditions in the Dirac's method